1991
DOI: 10.1143/jjap.30.l813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pt Addition on Melt-Processed YBaCuO Superconductors

Abstract: Platinum addition in precursors of melt processing could produce finely dispersed Y2BaCuO5 (211) inclusions of about 1 µm in YBa2Cu3O x matrix. This fine dispersion of 211 resembles that of quench-and-melt-grown materials. The platinum-added sample exhibited a critical current density exceeding 2×104A/cm2 at 77 K and 1 T. Platinum is considered to enhance the nucleation of 211 which forms by the pertitectic reaction between Y2O3 and liquid phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(34 citation statements)
references
References 4 publications
0
33
0
Order By: Relevance
“…The temperature behavior is proportional to the Ta molar fraction, as described in Eq. (6). It is suggested that the YTaBa phase is extremely diluted in the Y123 matrix and, as a direct consequence, the decrease in the peritectic temperature is clearly deduced.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The temperature behavior is proportional to the Ta molar fraction, as described in Eq. (6). It is suggested that the YTaBa phase is extremely diluted in the Y123 matrix and, as a direct consequence, the decrease in the peritectic temperature is clearly deduced.…”
Section: Resultsmentioning
confidence: 93%
“…Various investigations have focused on the melt process of the Y123 oxides [3]. It has been previously reported [4][5][6][7][8][9] that both alignment of grains and decreased grain boundaries are responsible for some improvements on the J c (critical current density).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was just before discovery of Bi-based superconducting material by Dr. Maeda et al [10]. Later on, it was revealed that a small amount of Pt resulted in fine 211 particles about 1μm in size [11][12][13].…”
Section: History Of Qmg and Qmg Bulk Magnetsmentioning
confidence: 99%
“…[2] In the melt-quenched powders, platinum is obtained through dissolution of the platinum crucible by the liquid melt. Since this is not possible in the non-quenched powders, a fine platinum powder is added prior to melt quenching.…”
Section: Fig 1 Single Crysmentioning
confidence: 99%